Silver-assisted Syntheses of Fused Five-membered N-heterocycles - Kaur, Navjeet; Ahlawat, Neha; Verma, Yamini; Grewal, Pooja; Bhardwaj, Pranshu; Jangid, Nirmala K. (Current Organic Chemistry, 2021)
The metal-mediated formation of heterocycles is one of the most emerging and important strategies in organic chemistry. The reactions utilized previously for the synthesis of heterocycles were less familiar to the scientists due to their complicated work-up, expensive nature, and difficult operations. The silver-assisted cyclic reactions are highly efficient for both regioselective and stereoselective syntheses of five-membered fused N-heterocyclic compounds. The applications of silver in the preparation of five-membered fused N-heterocyclic compounds are covered in this review article.
Keywords: synthesis